Penguatan Kapasitas Guru PAUD dalam Implementasi Seni dan Budaya Hindu - Wiasti, Ni Komang; Supartha, Ketut; Sumari, Made; Armayani, Ni Made Ria Taurisia (Universitas Muhammadiyah Mataram, 2026)
Abstract: This community service program aims to improve the capacity of Hindu early childhood teachers in West Nusa Tenggara to integrate Hindu arts and culture into early childhood education. The Pk Mini activity was motivated by teachers' low understanding of authentic Hindu arts and culture, limited integration skills, and the absence of a collaboration network. The activity was carried out through workshops and practice in dance, dharmagita, upakara, and Hindu-based storytelling with a participatory and educational approach for 30 teachers from various districts. The results of this PkM activity showed an increase in teachers' skills and the establishment of a collaboration network. This PkM program contributes to the preservation of Hindu culture, the strengthening of children's character, and the implementation of policies based on local wisdom. Recommendations for development include expanding the scope of participants to include teachers of early childhood education from different religions in order to strengthen social harmony, as well as ongoing assistance to support the design of an integrative thematic curriculum.Abstrak: Program pengabdian masyarakat ini bertujuan untuk meningkatkan kapasitas guru PAUD Hindu di Nusa Tenggara Barat dalam mengintegrasikan seni budaya Hindu ke dalam pembelajaran anak usia dini. Kegiatan Pk Mini Dilatarbelakangi oleh rendahnya pemahaman guru terhadap seni budaya Hindu autentik, terbatasnya keterampilan integrasi, serta belum adanya jejaring kolaborasi, kegiatan dilaksanakan melalui workshop dan praktik tari, dharmagita, upakara, dan storytelling berbasis budaya Hindu dengan pendekatan partisipatif dan edukatif terhadap 30 guru dari berbagai kabupaten. Hasil kegiatan PkM ini menunjukkan peningkatan keterampilan guru, terbangunnya jejaring kolaborasi. Program PkM ini berkontribusi pada pelestarian budaya Hindu, penguatan karakter anak, dan implementasi kebijakan berbasis kearifan lokal. Rekomendasi pengembangan mencakup perluasan cakupan peserta ke guru PAUD lintas agama guna memperkuat harmoni sosial, serta pendampingan berkelanjutan untuk mendukung perancangan kurikulum tematik integratif.